Optimising the routing of home health caregivers: can a hybrid ant colony metaheuristic provide a solution?. Issue 7 (2nd July 2020) - Euchi, Jalel
Abstract : Background/Aims: Consolidation of a unified health system requires the development of strategies that respond to various existing health needs, thus accommodating new and chronic conditions. Home care is a viable alternative to hospital care to meet the needs of the elderly population as well as those with other conditions that could be managed at home, which leads to a greater demand for home health services. One issue this raises is routing (assigning routes and transport) caregivers, where the goal is to minimise the total cost. Methods: A hybrid ant colony algorithm is proposed to solve the problem of routing home health care workers. The algorithm was tested in cases drawn from the literature and compared with works existing in the literature. Results: The algorithm provided good quality results with low computation times. Conclusions: The comparison results supported the efficacy of the suggested methodology, which can provide decision support for medical managers of home health care.